An Efficient Method for Vehicle License Plate Extraction - Marwan D., Saleh; H., Mellah; Ahmed, Mueen; N. D., Salih (2008)
License Plate Recognition (LPR) is a machine vision technology used to identify vehicles by their license plates without direct human intervention. This paper presents an efficient license plate extraction method which is mainly designed for Malaysian license plates recognition. Besides, it can be readily extended to cope with license plates of other countries, especially those using Latin characters. Our method is capable of extracting license plates in a concise manner, it works well on different types of Malaysian license plates and fast enough to be used in real-time. The method has been tested over a large number of images in order to analyze its performance. The test results, demonstrate that the proposed method is efficient to be used for the license plate recognition system.